Behaviour of parallel girders stabilised with U‐frames - Virdi, Kuldeep; Azzi, Walid (Journal of Civil Engineering and Management, 2010)
Lateral torsional buckling is a key factor in the design of steel girders. Stability can be enhanced by cross‐bracing, reducing the effective length and thus increasing the ultimate capacity. U‐frames are an option often used to brace the girders, when designing through type of bridges and where overhead bracing is not practical. This paper investigates the effect of the U‐frame spacing on the stability of the parallel girders. Eigenvalue buckling analysis was undertaken with four different spacings of the U‐frames. Results were extracted from finite element analysis, interpreted and conclusions drawn.First Published Online: 24 Jun 2011